2016
DOI: 10.1590/1678-4324-2016150170
|View full text |Cite|
|
Sign up to set email alerts
|

Recurrent Somatic Embryogenesis and Plantlet Regeneration in Psidium guajava L.

Abstract: A simple and efficient protocol for recurrent somatic embryogenesis and plant regeneration is one of the prerequisites

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
6
1
Order By: Relevance
“…According to Titon, Xavier, Otoni, and Motoike (2007), picloram is used for the induction of calli or the maintenance of cultures in suspensions, as well as for inducing the formation of embryogenic calli. Most studies have indicated that calli are achieved primarily through the use of 2,4-D (Bajpai, Kalim, Chandra, & Kamle, 2016;Fehér, 2015;Rocha et al, 2016;Winkelmann et al, 2015), including in the induction of calogenesis in Campomanesia rufa leaf explants (Sant'Ana, Paiva, Reis, Silva, & Silva, 2018), which was not found in the present study. Satisfactory results have been achieved using picloram for embryogenic callus induction in Eucalyptus grandis x E. urophylla (Moura et al, 2017) and Acca sellowiana (Cangahuala-Inocente, Caprestano, & Pierre, 2007), both from the same family, Myrtaceae, as gabiroba.…”
Section: Discussioncontrasting
confidence: 70%
“…According to Titon, Xavier, Otoni, and Motoike (2007), picloram is used for the induction of calli or the maintenance of cultures in suspensions, as well as for inducing the formation of embryogenic calli. Most studies have indicated that calli are achieved primarily through the use of 2,4-D (Bajpai, Kalim, Chandra, & Kamle, 2016;Fehér, 2015;Rocha et al, 2016;Winkelmann et al, 2015), including in the induction of calogenesis in Campomanesia rufa leaf explants (Sant'Ana, Paiva, Reis, Silva, & Silva, 2018), which was not found in the present study. Satisfactory results have been achieved using picloram for embryogenic callus induction in Eucalyptus grandis x E. urophylla (Moura et al, 2017) and Acca sellowiana (Cangahuala-Inocente, Caprestano, & Pierre, 2007), both from the same family, Myrtaceae, as gabiroba.…”
Section: Discussioncontrasting
confidence: 70%
“…During the first phase of embryo maturation, the presence of 30 g L -1 PEG-4000 in the culture medium favored the maturation of SE until the torpedo stage. Similarly PEG-3350 (50 g L -1 ) stimulated the development and maturation of SEs of Myrciaria aureana, another Myrtaceae species (Motoike et al 2007). Bajpai et al (2016 used the same concentration for SE maturation of Psidium guajava and obtained 74.38% of cotyledonary embryos.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that higher concentrations (5 μM) of 2,4-D favored tissue differentiation and somatic embryo formation. It is observed in the literature that the use of 2,4 -D individually has greater success (Bajpai et al 2016, Kamle andBaek 2017). Luis and Scherwinski-Pereira (2014) efficiently induced embryogenic callus formation in Acrocomia aculeate by using low concentration of 2,4-D (1.5 mg L -1 ).…”
Section: Mcr Araújo Et Almentioning
confidence: 99%